Silent pheochromocytoma and paraganglioma: Systematic review and proposed definitions for standardized terminology - Constantinescu, Georgiana; Preda, Cristina; Constantinescu, Victor; Siepmann, Timo; Bornstein, Stefan R.; Lenders, Jacques W. M.; Eisenhofer, Graeme; Pamporaki, Christina (Frontiers in Endocrinology, 2022)
Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors with heterogeneous clinical presentations and potential lethal outcomes. The diagnosis is based on clinical suspicion, biochemical testing, imaging and histopathological confirmation. Increasingly widespread use of imaging studies and surveillance of patients at risk of PPGL due to a hereditary background or a previous tumor is leading to the diagnosis of these tumors at an early stage. This has resulted in an increasing use of the term “silent” PPGL. This term and other variants are now commonly found in the literature without any clear or unified definition. Among the various terms, “clinically silent” is often used to describe the lack of signs and symptoms associated with catecholamine excess. Confusion arises when these and other terms are used to define the tumors according to their ability to synthesize and/or release catecholamines in relation to biochemical test results. In such cases the term “silent” and other variants are often inappropriately and misleadingly used. In the present analysis we provide an overview of the literature and propose standardized terminology in an attempt at harmonization to facilitate scientific communication.